Energy flexibility of domestic thermal loads – a building typology approach of the residential building stock in Austria. Issue 1 (2nd January 2019) - Weiß, Tobias; Fulterer, Anna Maria; Knotzer, Armin
ABSTRACT: Due to a high share of fluctuating renewables in the energy system and many grid-connected heating systems, Austria is facing a growing problem of peak loads in electric and thermal grids [E-Control Austria (2015). Market Report – National Report to the European Commission, Retrieved from https://www.econtrol.at/documents/20903/443907/EC_Marktbericht15_ENGL.pdf/e22b1ce5-a8c9-44bf-a701-0a73af678735 ]. Based on the research done in the framework of EBC Annex 67 Energy Flexible Buildings [Jensen, S. (2015). IEA EBC Annex 67 Energy Flexible Buildings – Annex Text. www.annex67.org ], theoretical and practical considerations about the potential contributions of domestic heat loads to energy flexibility are drawn for building typologies in Austria TABULA. (2009–2012). Typology approach for building stock energy assessment/IEE EPISCOPE Project. Retrieved from http://www.episcope.eu/ieeproject/tabula/ ]. In order to explore the potential of energy flexibility of residential buildings that can be used without jeopardizing building comfort, various building models have been simulated in IDA ICE. Connections between energy flexibility related to the building's technical equipment, its construction period, physical characteristics, climate and user comfort are analysed. The evaluation shows which individual technologies and parametric optimizations are recommended for load management. The results show that in buildings built according to Austrian standards after 1980 at least 50% of domestic heating peak loads can be shifted to off-peak periods.